Research on the three-phase load imbalance control of the active distribution network based on the distributed power flow controller - Guo, Guowei; Zhan, Ximei; Wang, Jinfeng; Liu, Zhu; Feng, KangHeng; Peng, Fadong; Gong, Dehuang; Tang, Aihong; Xiang, Caili; Wang, Zihan (Frontiers in Energy Research, 2024)
Under the background of global commitment to low-carbon renewable energy transformation, new energy sources such as distributed wind-solar storage and charging and single-phase loads such as electric vehicles are connected to the distribution network. Due to the asymmetric access of load and the randomness of load power consumption, the problem of three-phase imbalance is becoming more and more prominent and the uncertainty is increasing. In this paper, by analyzing the three-phase load imbalance problem of distribution network, starting from the cause of three-phase load imbalance, the three-phase imbalance calculation method of distribution network is deduced. The access mode of distributed power flow controller in distribution network and the three-phase imbalance compensation method are studied. The control strategy of distributed power flow controller for threephase imbalance control of distribution network is proposed. The simulation results show that the proposed method can effectively control the three-phase asymmetry problem of distribution network, and the configuration is more flexible and the capacity utilization rate is higher.